Da desistência do recurso especial repetitivo representativo da controvérsia - Sato, Juliana Laurenti (2013)
The raising number of cases that are reaching the High Courts made the legislator look for processual techniques which guarantee constitucional principles, such as legal certainty and effectiveness and in addition to allow those courts to worry only about the imposed functions: safeguard the constitution and judge violations of the non-constitucional legislation. Among these techniques we can highlight the trial judgment in the repetitive special remedies, of which the resulting decision will serve as orientation for all the other pending remedies that are waiting. However, the adoption of this technique has violated subjective right of the part, specifically the possibility of withdrawal of representative remedy of the controversy, which is why the position already adopted by the Superior Court is discoursed, in the sense of refusing the request to dropout that show at odds with the position already adopted by the Supreme Court, also tapped to examine alternatives and innovations that can be adopted with the approval of the New Code of Civil Procedure Draft